2022
DOI: 10.3390/ijms232315332
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Altered Hemorheological and Hematological Parameters during One-Month Observation Period in Critically Ill COVID-19 Patients

Abstract: Hematological and hemorheological parameters are known to be altered in COVID-19; however, the value of combined monitoring in order to deduce disease severity is only scarcely examined. A total of 44 acute SARS-CoV-2-infected patients (aCOV) and 44 age-matched healthy controls (Con) were included. Blood of aCOV was sampled at admission (T0), and at day 2 (T2), day 5 (T5), day 10 (T10), and day 30 (T30) while blood of Con was only sampled once. Inter- and intra-group differences were calculated for hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 72 publications
2
13
0
2
Order By: Relevance
“…This study also found a correlation of the level of inflammatory blood values and D-dimers with right ventricular dysfunction. Therefore, thromboembolic and vasculitic mechanisms are also discussed in this patient population, which seems reasonable, as haematological, inflammatory and rheological changes occur under COVID-19 and often persist for a long time [ 11 , 39 ].…”
Section: Strain In the Diagnostic Work-up Of Post-covid Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…This study also found a correlation of the level of inflammatory blood values and D-dimers with right ventricular dysfunction. Therefore, thromboembolic and vasculitic mechanisms are also discussed in this patient population, which seems reasonable, as haematological, inflammatory and rheological changes occur under COVID-19 and often persist for a long time [ 11 , 39 ].…”
Section: Strain In the Diagnostic Work-up Of Post-covid Syndromementioning
confidence: 99%
“…Arrhythmias and stress cardiomyopathies have also been described and affect patient prognosis [8,9]. The pathogenesis is diverse including viral endothelitis, humoral and prothrombotic changes and systemic inflammatory response syndrome [10][11][12]. In particular, the co-expression of Arrhythmias and stress cardiomyopathies have also been described and affect patient prognosis [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have revealed increased aggregation of erythrocytes in patients with COVID-19 [1][2][3][4][5][6]. The precise mechanisms underlying this phenomenon have not yet been entirely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the research indicates the role of plasma as a factor influencing aggregation in COVID-19 [1][2][3][4][5]. Despite its importance, focusing solely on fibrinogen and other plasma factors can overlook the potential influence of cellular factors on erythrocyte aggregation [7], while in the context of COVID-19, it is necessary to fully understand the contribution of both plasma and cellular factors to changes in erythrocyte aggregation.…”
Section: Introductionmentioning
confidence: 99%